Tax and the labour market: taxing personal services income in the UK - Oats, Lynne; Sadler, Pauline (Curtin Business School, 2008)
In March 1999, the UK Inland Revenue (now Her Majesty’s Revenue & Customs) issued a press release (IR35) announcing changes designed to counter perceived tax avoidance through the use of intermediaries to disguise employment relationships. This paper examines the implementation of these changes, demonstrating that resistance to a proposedfiscal measure can influence the way in which it is eventually enacted. Reference is made to the Welfare Reform and Pension Bill: Regulatory Impact Assessment (1999), the Professional Contractors Group, and The Queen & Commissioners of Inland Revenue ex parte (1) Professional Contractors Group Ltd (2) Ruud van Zundert (3) Square Mile Projects Ltd.